2021
DOI: 10.3390/nu13114039
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Weight Status in Italian Preschoolers with Autism Spectrum Disorder and Typically Developing Children

Abstract: Atypical eating habits are more common in children with autism spectrum disorders (ASD) than typically developing (TD) peers. Feeding problems may lead to the double burden of specific nutrient deficiencies and excessive weight gain, with a consequent increase in obesity prevalence. The dietary intake of Italian preschoolers with ASD compared to their TD peers and the impact of their dietary choices on their weight status and relationship to food selectivity (FS) were investigated. Dietary patterns and their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
12

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 79 publications
2
15
0
12
Order By: Relevance
“…In the current study, there was no significant difference in the frequency of SSBs intake between children with ASD and TD children. Inconsistent with our study, some studies showed that compared to TD children, children with ASD tended to intake more SSBs and sugars (10,11,38). A study with a large sample among Chinese children aged 6-17 years showed that only 24.50% of the children consumed SSBs <1 time /week, and 25.90% consumed SSBs ≥5 times/week (39).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the current study, there was no significant difference in the frequency of SSBs intake between children with ASD and TD children. Inconsistent with our study, some studies showed that compared to TD children, children with ASD tended to intake more SSBs and sugars (10,11,38). A study with a large sample among Chinese children aged 6-17 years showed that only 24.50% of the children consumed SSBs <1 time /week, and 25.90% consumed SSBs ≥5 times/week (39).…”
Section: Discussionsupporting
confidence: 77%
“…It has been well documented that SSBs intake has harmful effects on children health, such as obesity, dental caries, high blood pressure, metabolic syndromes, diabetes and cardiovascular diseases ( 9 ), and emotional and behavioral problems ( 5 ). Some studies have shown that compared to TD children, children with ASD tend to intake more SSBs and sugars due to refuse bitter taste during the period of preschool and primary school ( 10 , 11 ). Unfortunately, children with ASD were vulnerable to diet ( 12 ), so we speculated that higher frequent SSBs intake was positively associated with emotional and behavioral problems in the children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…[ 33 ] found that children who live in low UVB light have almost three times the prevalence of ASD compared to children who live in sunny areas. Moreover, ASD children may show particular dietary habits, often having food selectivity and restricted diets, which expose them to an increased risk for micronutrient deficiencies [ 34 ]; thus, 25(OH)D synthesis or intake may be reduced in these children.…”
Section: Discussionmentioning
confidence: 99%
“…Uma criança com uma boa alimentação tem menos probabilidade de sofrer: distúrbios nutricionais, anemia, sobrepeso, obesidade, cárie dentária e problemas de aprendizagem escolar, contribuindo para a prevenção de certas patologias na idade adulta como doenças cardiovasculares, diabetes e alguns tipos de câncer (Raspini et al, 2021).…”
Section: Oliveira E Souza 2022unclassified